2014
DOI: 10.1080/00032719.2013.867499
|View full text |Cite
|
Sign up to set email alerts
|

Laccase Biosensor Based on Graphene-Chitosan Composite Film for Determination of Hydroquinone

Abstract: A novel laccase biosensor was fabricated by entrapping laccase in graphene-chitosan composite materials and applied to determine hydroquinone. The graphene-chitosan composite had good conductivity, high stability, and good biocompatibility. Laccase was firmly embedded into the composite without other cross-linking reagents. The morphology and electrical conductivity of graphene-chitosan film were measured by scanning electron microscopy and electrochemical impedance spectroscopy. This biosensor catalyzed the o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
6
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 26 publications
0
6
0
Order By: Relevance
“…However, the direct immobilization of redox active enzymes on GR surface is difficult due to its strong hydrophobic nature and the presence of only sp 2 hybridized carbon atoms28. Hence, the GR based composites have been largely used for the immobilization of laccase293031. It is reported earlier that the carbohydrate polymers and surfactants dispersed GR has been used as a potential material for immobilization of range of redox active proteins including laccase31.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, the direct immobilization of redox active enzymes on GR surface is difficult due to its strong hydrophobic nature and the presence of only sp 2 hybridized carbon atoms28. Hence, the GR based composites have been largely used for the immobilization of laccase293031. It is reported earlier that the carbohydrate polymers and surfactants dispersed GR has been used as a potential material for immobilization of range of redox active proteins including laccase31.…”
mentioning
confidence: 99%
“…Hence, the GR based composites have been largely used for the immobilization of laccase293031. It is reported earlier that the carbohydrate polymers and surfactants dispersed GR has been used as a potential material for immobilization of range of redox active proteins including laccase31. In addition, carbohydrate polymers have highly enriched with hydrophilic chemical groups on GR and result into the formation of water soluble GR hybrids32.…”
mentioning
confidence: 99%
“…7 indicated that peak height increases linearly with the hydroquinone concentration in the range of 1-50 µM, while the sensitivity was 0.3523 mV µM -1 (see inset (a)). The limit of detection (LOD) was 0.1 µM which was lower than 0.26 µM of entrapping laccase in graphene-chitosan composite materials [7] and 2 µM of laccase immobilization onto 1-aminopyrene functionalized reduced graphene oxides (rGOs)-modified glassy carbon electrode by encapsulation with chitosan [29]. 11 …”
Section: Performance Of the Proposed Systemmentioning
confidence: 99%
“…In recent years, many articles reported the development of electrochemical methods for hydroquinone determination [7][8][9][10] Qu et al fabricated a novel laccase biosensor by entrapping laccase in graphene-chitosan composite materials and applied to determine hydroquinone [7]. Wu et al developed a novel photo-electrochemical sensor for determination of hydroquinone [8].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation